How Fast Tobacco Can Be: The Logistical Process at Rothmans of Pall Mall Indonesia in the 1997 Indonesian Economic Crisis - Heijden, R.J.E. van der; Wagner, B.G.; Sukoharsono, E. G. (Accounting Department,, 2004)
Every year Rothmans International Group publishes a geographical business report. In this report the different Asian geographical regions are compared with one another concerning profit, costs, sales etc. Before 1996, Rothmans of Pall Mall Indonesia was always at the 1st place concerning profit. This is because of the low costs spent in Indonesia. In 1996 profits were declining and their place at the hit list was taken by Malaysia. This wakened the management in Jakarta and Malang. The Profit numbers were still declining due the higher costs than expected (sales maintain constant). The costs increased in the year of 1996 with 10% (usually between 4% and 6%). Those 10% total for a RP 2,6 billion: 1996.